Proportion Of Daily Abundance Of Phytoplankton Based On Time Changes In Periods Of The Best Incubation Time In Marine Waters - Rahmadi Tambaru; Arniati Massinai; Khairul Amri; Amran Saru; Erwin Pratama Umar (Barakuda'45, 2022)
The research aimed to analyzing the proportion of the daily abundance of phytoplankton based on the change in time in the best incubation time period. The implementation of the research from November 2018 to January 2019 in the marine waters of Barrang Lompo Island. Water samples to identify the daily phytoplankton abundance were taken by filtering 100 liters of seawater using a plankton net. Water sampling was carried out at the observation time at 10:00; 11.00; 12.00; 13.00; 14.00 in the best incubation time period (10.00-14.00). Based on the results of the study, the change in the proportion of daily phytoplankton abundance did not differ significantly based on the change in time in the best incubation time period.